(untitled) (International Journal of Engineering and Computer Science, 2018)
This paper presents an experimental design of adaptive algorithms to investigation of Symbol error rate for adaptive training algorithms without involving with any modified or design algorithms, two conventional adaptive equalizer training methods, the least mean squares (LMS) and recursive least squares (RLS), are implemented in a Quadrature amplitude modulation over sampled received sequence and their performances are compared in different parameters like symbol size, step size and rotation. The algorithms were evaluated using convergence SER at SNR of 20 dB over different number of iterations to determine the convergence rate and constellation diagra